SAMBAS INTERNATIONAL ISLAMIC CENTER - Gebi Gebi; Irwin Irwin; Lestari Lestari (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Islam developed rapidly in Sambas Regency during the era of the Sambas Sultanate of Sultan Muhammad Syafiuddin II (1688-1922) and was nicknamed